Impact of light soaking and thermal annealing on amorphous silicon thin film performance. (10th February 2015) - Pierro, M.; Bucci, F.; Cornaro, C.
Abstract: Nowadays, there is a wide debate in literature related to the silicon thin films seasonal performance. Amorphous modules seem to react positively to the temperature, while the temperature parameters indicate a negative thermal response. Periodic fluctuations of nominal power due to light soaking and thermal annealing effects are observed. On the other hand, the module temperature reached in some open rack plants seems too low to activate annealing power regeneration process so that the seasonal performance trend may depend mainly on other effects such as spectral or irradiance. In the following paper, a model that allows to calculate the impact of all the phenomena that affect the photovoltaic performance is used. The light soaking and thermal annealing contributions are measured from outdoor data using two different methods. Both methods lead to similar results, and the model is able to reproduce the seasonal performance with an acceptable level of reliability on the day, hour, minute time scale. An analysis of each effect contribution to the seasonal performance is also provided. Thus, main open questions related to a‐Si thin films performance such as positive reaction to temperature and seasonal fluctuations are discussed. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Two methods (separate and direct)are used to describe thermal annealing and light soaking effects (SWE) of an amorphous DJ silicon module. Thermal annealing compensate the intrinsic thermal coefficients of the module producing an overall positive reaction to temperature on the seasonal time scale. SWE is the main effect contribution to the module performance at Rome latitude consisting in a seasonal PR fluctuation of 7%.